Wheat - Ansari, Mahmood-ur-Rahman (IntechOpen, 2022)
This book deals with diverse topics in wheat research and production. It discusses advances in biotic and abiotic stress tolerance in wheat, especially under climate change conditions. The chapters present valuable information regarding wheat diseases, insect pests, and various environmental stresses.